A IDENTIFIKASI PERSENTASE UPAH HASIL MAKELAR DARI PENJUAL DAN PEMBELI SEBIDANG TANAH - zakiyah, lizatul; M. Masrukhan (Lembaga Berugak Baca, 2024)
A broker is defined as an intermediary between bothparties, sellers and buyers who mutually pledge or enter into a contract to offer any goods/objects, including a plot of land. The size of the income earned by the broker depends on his efforts and good work. If the broker can sell land with good work, then the broker's income will also be large. However, sometimes the price agreed upon by the broker and the buyer does not provide the right information to the land owner at the broker's request. In this research, the author uses qualitative research methods by identifying, describing and analyzing the distribution of brokers' profits in a sale and purchase transaction of a plot of land. As an intermediary between sellers and buyers of land, accepting and servicing every job in order to use their services as an intermediary, apart from that, a broker sometimes has the task of checking the validity of the certificate itself. In this case, a broker plays a very important role in selecting potential buyers.